Perkembangan Control Foreign Corporation (CFC) Rules di Indonesiadalam Upaya Mengamankan Penerimaan Negara dari Sektor Pajak - Ning Rahayu, Ning Rahayu (Jurnal Vokasi Indonesia, 2017)
Economic globalization has had the effect of increasing international transactions by multinational corporations. In an effort to achieve optimal profit, the multinational company's companies make various efficiency efforts, both done in legal and illegal ways. The effort is to avoid international tax evasion. One of the forms of tax evasion is through the Control Foreign Corporation (CFC) scheme, ie tax evasion efforts by delaying the recognition of income from foreign- derived capital (especially in tax-haven countries) to be taxed domestically. Tax evasion practices with this scheme can undermine state revenues from the tax sector. For the Indonesian state that makes the tax revenue as the prima donna of state revenue, this is a serious concern. Therefore, to counteract the practice of tax avoidance, the Indonesian state makes CFC Rules. CFC Rules in Indonesia have been renewed several times in an effort to close these tax avoidance opportunities as well as to secure state revenues from the tax sector.